Evaluation of combustion characteristics, performance and exhaust emission for diesel fuel with various type nano particle blends - Ang, Fuk Chen (2021)
This research investigates the effect of nanoparticles (aluminium oxides, carbon nanotubes and silicone oxide) blend in diesel fuel on physio-chemical properties, combustion characteristics, performance and exhaust emission of a four-stroke single cylinder engine with direct injection. Nanoparticle is widely use as additive due to its high surface to volume ratio thus have better thermal properties. But most the past literatures only focus on single nanoparticle instead of mixture of nanoparticle. So this research will utilise response surface methodology to determine the best blend ratio of the three nanoparticles. Beside that nanoparticle is very expensive to produce, so optimal concentration of each nanoparticle in diesel fuel was determined by using Box-Behnken’s response surface methodology to maximise the performance and reduce emission of diesel fuel. The nanoparticles were dispersed in a dosage of 25, 50 and 100 ppm in pure diesel fuel using ultrasonic processor for 30 minutes. Aluminium oxides (Al2O3) and carbon nanotubes (CNT) fuel blends show reduction of kinematic viscosity by 9.6 to 18.8 % compared to diesel fuel. Meanwhile, the calorific value increased by 4.12 % with CNT blends. However, the cetane number was remain with additional of the nanoparticles. The blend fuels were experimentally tested with YANMAR TF120M single cylinder four-stroke diesel engine at engine load of 0, 25, 50, 75 and 100 % of 5.9 bar brake main effective pressure (BMEP) at a constant 1500 rpm engine speed. The results revealed that the brake specific fuel consumption (BSFC) showed reduction up to 19.8 % while 18.8 % enhancement shown in brake thermal efficiency (BTE). Next, the model from response surface methodology (RSM) was used for optimization with an objective of minimizing the fuel consumption, CO, CO2, NOX and HC emissions. Utilizing this approach, the blend fuel with 100 ppm Al2O3 and 100 ppm CNT with 79.13 ppm SiO2 was considered to deliver optimum emission and performance characteristics with a maximum desirability of 0.9846 at 25% engine load.